Drug-induced Esophagitis - Pande Made Juniarta; I Dewa Nyoman Wibawa (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Esophageal injury could be caused by a various etiology, such as drug administration. Drug-induced esophagitis is a spectrum of esophageal lesions due to drugs that can cause complications of ulceration, perforation and stricture of the esophagus. More than one hundred drugs have been identified to cause damage to the esophageal wall, such as antibiotics, nonsteroidal anti inflammatory drugs (NSAID), alendronate, potassium chloride, anti-hypertension, quinidine, etc. Symptoms of drug induced esophagitis might appear as retrosternal pain, heartburn, odynophagia, dysphagia, weight loss, gastrointestinal bleeding, which also found in other cases of gastrointestinal lesions so they are often misdiagnosed in daily clinical practice. Endoscopic procedure is the first choice in diagnosis of drug-induced esophagitis. The lesion may appear as erosion, bleeding, ulcers, strictures, kissing ulcers, and residual drugs fragment on endoscopy. Management of drug-induced esophagitis are by stopping suspected drugs and educating about the proper drug administration. In severe cases, adequate fluid hydration and parenteral nutrition can be given. Sucralfat forms a protective layer in the area of the lesion, thus accelerates wound healing process. Acid-lowering agents can be considered in cases of reflux esophagitis. Therapeutic endoscopic may indicated in strictures cases, active bleeding due to esophageal ulcers, and retrieval remaining drug fragments that are lodged in the esophagus. While surgery should be reserved for patients with severe complications such as erosion of the mediastinal organs, heart and large blood vessels